Individual responses to a single oral dose of albendazole indicate reduced efficacy against soil-transmitted helminths in an area with high drug pressure. - Martin Walker; Piet Cools; Marco Albonico; Shaali M Ame; Mio Ayana; Daniel Dana; Jennifer Keiser; Leonardo F Matoso; Antonio Montresor; Zeleke Mekonnen; Rodrigo Corrêa-Oliveira; Simone A Pinto; et al. (Public Library of Science (PLoS), 2021)
Background Albendazole (ALB) is administered annually to millions of children through global deworming programs targeting soil-transmitted helminths (STHs: Ascaris lumbricoides, Trichuris trichiura and hookworms, Necator americanus and Ancylostoma duodenale). However, due to the lack of large individual patient datasets collected using standardized protocols and the application of population-based statistical methods, little is known about factors that may affect individual responses to treatment. Methodology/principal findings We re-analyzed 645 individual patient data from three standardized clinical trials designed to assess the efficacy of a single 400 mg oral dose of ALB against STHs in schoolchildren from different study sites, each with varying history of drug pressure based on duration of mass drug administration programs: Ethiopia, low; Lao People's Democratic Republic (PDR), moderate; Pemba Island (Tanzania), high. Using a Bayesian statistical modelling approach to estimate individual responses (individual egg reduction rates, ERRi), we found that efficacy was lower in Pemba Island, particularly for T. trichiura. For this STH, the proportion of participants with a satisfactory response (ERRi ≥50%), was 65% in Ethiopia, 61% in Lao PDR but only 29% in Pemba Island. There was a significant correlation between ERRi and infection intensity prior to drug administration (ERRi decreasing as a function of increasing infection intensity). Individual age and sex also affected the drug response, but these were of negligible clinical significance and not consistent across STHs and study sites. Conclusions/significance We found decreased efficacy of ALB against all the STHs analyzed in Pemba Island (Tanzania), an area with high drug pressure. This does not indicate causality, as this association may also be partially explained by differences in infection intensity prior to drug administration. Notwithstanding, our results indicate that without alternative treatment regimens, program targets will not be achievable on Pemba Island because of inadequate efficacy of ALB. Trial registration The study was registered on Clinicaltrials.gov (ID: NCT03465488) on March 7, 2018.